Magnesium alloy hydrogel composite scaffold
Through the soft-hard-bonding design and electrochemical combination of magnesium alloy hydrogel composite scaffolds, the problem of easy deformation of existing scaffolds and lack of adsorption on the bonding surface is solved, and higher mechanical strength and fatigue resistance are achieved, ensuring the stability and effect of osteocartilage defect repair.
Patent Information
- Application Number
- CN202411680074.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-04-29
AI Technical Summary
The existing stents for bone-cartilage defect repair are prone to deformity, and the bonding surface between the cartilage layer and the subchondral bone layer lacks adsorption force, resulting in easy shear force generated during the in vivo repair process, affecting the repair effect.
The magnesium alloy hydrogel composite scaffold is adopted, including a porous magnesium alloy scaffold and a hydrogel cartilage layer that simulates normal clear cartilage components. The mechanical strength and fatigue resistance of the scaffold are improved through the soft and hard combination structure, and the stability of the scaffold is enhanced through electrochemical binding.
The Young's modulus of the hydrogel is improved, the mechanical strength and fatigue resistance of the scaffold are enhanced, and the stability and integration of the scaffold are ensured during the repair process, avoiding deformation and separation.
Smart Images

Figure CN119896764A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of osteochondral defect repair, and in particular to a magnesium alloy hydrogel composite scaffold. Background Art
[0002] Osteochondral defects are a major problem in clinical treatment, and the incidence rate is increasing. Since cartilage has no blood vessels or nerves, its self-repair ability is limited. Current clinical treatments often include microfracture surgery and autologous osteochondral transplantation, but the treatment effect is often limited. Therefore, many basic studies are currently focused on constructing composite biological scaffolds to treat osteochondral defects in clinical practice. Since the mechanical strength and biological effects of cartilage and subchondral bone are quite different, the cartilage layer and subchondral bone layer of the composite scaffold must have different compositions and functions; however, most of the studies simply stack the cartilage layer scaffold and the subchondral bone layer scaffold together to form a composite scaffold. The limitation of this scaffold is that during the in vivo repair process, there is almost no adsorption force on the two-layer bonding surface, which will generate shear force in the horizontal or other directions of the bonding surface, thereby ignoring the braking and repair effect of the calcified cartilage interlayer between the cartilage and the subchondral bone layer; and since the location of osteochondral is almost always a position that requires repeated pressure buffering, if the composite scaffold is simply stacked, it will deform or even separate due to repeated compression. Summary of the invention
[0003] One purpose of the present invention is to provide a magnesium alloy hydrogel composite scaffold to solve the problem that the existing scaffolds used for repairing osteochondral defects are easily deformed.
[0004] A magnesium alloy hydrogel composite stent, comprising:
[0005] A magnesium alloy bracket having a porous structure;
[0006] A hydrogel cartilage layer, the surface of which is in contact with the magnesium alloy stent, and the hydrogel cartilage layer comprises methacrylated gelatin hydrogel, methacrylated hyaluronic acid hydrogel and methacrylated chitosan hydrogel.
[0007] Optionally, a portion of the hydrogel cartilage layer in contact with the magnesium alloy stent is embedded in a hole on the surface of the magnesium alloy stent through deformation.
[0008] Optionally, the pore size of the magnesium alloy support ranges from 300 to 600 μm.
[0009] Optionally, the magnesium alloy bracket is a porous magnesium alloy bracket with a Gyroid structure.
[0010] Optionally, the magnesium alloy bracket comprises the following components in mass fraction:
[0011] Mg: 96.5-97%;
[0012] O: 0.9~0.92%;
[0013] Y: 1.05~1.15%;
[0014] Nd: 0.80~0.85%;
[0015] Zr: 0.08-0.12%;
[0016] Gd: 0.3~0.33%.
[0017] Optionally, the water content of the methacrylylated gelatin hydrogel, the methacrylylated hyaluronic acid hydrogel and the methacrylylated chitosan hydrogel is 85-95%.
[0018] Optionally, the weight ratio of methacryloylated gelatin hydrogel: methacryloylated hyaluronic acid hydrogel: methacryloylated chitosan gel hydrogel in the hydrogel cartilage layer is 0.9-1.1: 0.9-1.1: 0.9-1.1.
[0019] Optionally, the method for preparing the hydrogel cartilage layer comprises the following steps:
[0020] Step 1) using an aqueous solution containing a light curing agent to dissolve methacrylated gelatin dry powder, methacrylated hyaluronic acid dry powder, and methacrylated chitosan dry powder respectively to obtain methacrylated gelatin gel solution, methacrylated hyaluronic acid gel solution, and methacrylated chitosan gel solution;
[0021] Step 2) Mixing the methacrylated gelatin gel solution, the methacrylated hyaluronic acid gel solution and the methacrylated chitosan gel and subjecting them to photocuring treatment to obtain the hydrogel cartilage layer.
[0022] Optionally, the magnesium alloy stent and the hydrogel cartilage layer are both cylindrical; the top surface of the magnesium alloy stent is in contact with the bottom surface of the hydrogel cartilage layer.
[0023] A device for repairing osteochondral defects comprises the above-mentioned magnesium alloy hydrogel composite scaffold.
[0024] Compared with the prior art, the present invention has at least the following beneficial effects:
[0025] The present invention proposes a magnesium alloy hydrogel composite scaffold, comprising: a porous magnesium alloy scaffold and a hydrogel cartilage layer. The formula of the cartilage layer of the present invention simulates the composition of normal hyaline cartilage; and the Young's modulus of the hydrogel is further improved by the unique structure of soft and hard combination, which is increased by about 3 times to meet the mechanical strength of normal physiological cartilage. The particularity of the soft and hard combination also improves the fatigue resistance of the hydrogel. In addition, the combination of magnesium alloy and hydrogel further forms an electrochemical bond, making the combination more compact. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0027] Figure 1 It is a schematic diagram of the compression effect of the embodiment of the present invention and the comparative example.
[0028] Figure 2 It is a graph showing the test results of Young's modulus of the embodiments of the present invention and the comparative examples.
[0029] Figure 3 It is a diagram of the anti-fatigue test results of the embodiments of the present invention and the comparative examples.
[0030] Figure 4 It is the infrared spectrum analysis result figure of the embodiment of the present invention and comparative example.
[0031] Figure 5 The storage modulus and loss modulus test results of each gel sample are shown in FIG.
[0032] Figure 6 The graph shows the Young's modulus test results of each gel sample. DETAILED DESCRIPTION
[0033] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.
[0034] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0035] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention.
[0036] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0037] The present invention provides a magnesium alloy hydrogel composite scaffold which is mainly divided into three parts, wherein the cartilage layer is composed of hydrogel, the subchondral bone layer is composed of porous magnesium alloy, and the bonding surface is a unique soft-hard bonding design. In the process of simulating the in vivo motion environment, the cartilage layer will be compressed, thereby further compressing the subchondral bone; the cartilage layer gel will be partially embedded into the pores of the lower magnesium alloy due to compression, thereby forming a unique interlocking structure, which can not only improve the mechanical strength of the upper gel, but also improve the fatigue resistance of the gel by increasing the bonding sites. In addition, the bonding surface will be more stable, so that the composite scaffold maintains integrity during the repair process.
[0038] The cartilage layer of the magnesium alloy hydrogel composite scaffold of the present invention is formed by mixing three kinds of hydrogels, and is formed into a gel of the cartilage layer by light curing technology. The three kinds of gels are: methacryloyl gelatin (GelMA), methacryloyl hyaluronic acid (HAMA), and methacryloyl chitosan (CSMA). Natural hyaline cartilage is mainly composed of 70%-80% water, chondroitin sulfate, hyaluronic acid, and collagen. The water content of the three hydrogels reaches more than 80%. HAMA is rich in hyaluronic acid; the chondroitin sulfate contained in CSMA is a key proteoglycan in natural cartilage; GelMA contains a natural collagen structure, which can provide matrix support, pore connection and cell migration conditions similar to those of natural hyaline cartilage. Therefore, the presence of the three ratios can simulate the key components of natural hyaline cartilage and provide a microenvironment suitable for the growth and function of chondrocytes.
[0039] The composition of the subchondral bone layer of the magnesium alloy hydrogel composite scaffold of the present invention is: a porous magnesium alloy scaffold composed of a Gyroid structure, which together with the cartilage layer gel forms a cylindrical composite scaffold with a height of 5 mm and a diameter of 5 mm. The pore size range of the magnesium alloy scaffold is 300-600 μm, and such parameters are formulated based on the pore size range of normal trabecular bone (300-600 μm), which will make the bone layer magnesium alloy scaffold more in line with the bionic microenvironment of the subchondral bone.
[0040] The magnesium alloy hydrogel composite scaffold of the present invention adopts a soft-hard combination structure: the existing structures are all simple stacking types, and the uniqueness of this design is that the lower layer is composed of a porous structure. Due to the rheological properties of the upper layer gel, the lower part will produce partial deformation in the process of simulating cartilage buffering, achieving interlocking and embedding with the porous structure, which will increase the specific surface area and binding sites, not only increasing the adhesion of the upper and lower layers, but also helping to disperse the external stress into a larger volume, reducing local stress concentration and fatigue damage. In addition, the porous structure also provides more deformation buffer space for the gel to prevent excessive local deformation from causing structural damage.
[0041] Example 1
[0042] Preparation of hydrogel cartilage layer:
[0043] An aqueous solution of the photoinitiator Lap was prepared with a concentration of 0.5 wt %.
[0044] 100 mg of methacrylated gelatin powder (GelMA), methacrylated hyaluronic acid powder (HAMA), and methacrylated chitosan powder (CSMA) were weighed and dissolved in 1 ml of the aqueous solution of the above-mentioned photoinitiator Lap; the mixed solution was then placed in a 40°C water bath in a light-proof environment for 20 minutes to prepare methacrylated gelatin gel solution, methacrylated hyaluronic acid gel solution, and methacrylated chitosan gel solution.
[0045] The methacrylated gelatin gel solution, methacrylated hyaluronic acid gel solution, and methacrylated chitosan gel solution were mixed in a ratio of 1:1:1, and then transferred to a cylindrical mold with a height of 1.5 mm and a diameter of 5 mm. A 405 nm ultraviolet light source was used to irradiate the mold for 20 seconds to cure the photocurable groups in the mixed gel, thereby finally obtaining a cylindrical hydrogel cartilage layer.
[0046] Preparation of Gyroid structure porous magnesium alloy scaffold:
[0047] A porous magnesium alloy bracket with a Gyroid structure is 3D printed using magnesium alloy material. The raw material components of the magnesium alloy are Mg: 96.75%; O: 0.91%; Y: 1.10%; Nd: 0.82%; Zr: 0.10%; and Gd: 0.31%.
[0048] A porous magnesium alloy stent with a cylindrical Gyroid structure with a pore size of 500 μm (bionic design for the pore size of trabecular bone), a height of 3.5 mm and a diameter of 5 mm was obtained.
[0049] The preparation of the hydrogel cartilage layer is set on a Gyroid structure porous magnesium alloy scaffold, and the hydrogel cartilage layer and the cartilage layer gel together constitute a composite scaffold with a height of 5 mm and a diameter of 5 mm.
[0050] Example 2
[0051] Compared with Example 1, the raw material ratio of the hydrogel cartilage layer in this example is adjusted to a mixture of methacrylated gelatin gel solution, methacrylated hyaluronic acid gel solution, and methacrylated chitosan gel solution in a ratio of 1.1:0.9:0.9. The pore size of the Gyroid structure porous magnesium alloy scaffold is changed to 300 μm, and the other steps are the same as in Example 1.
[0052] Example 3
[0053] Compared with Example 1, the raw material ratio of the hydrogel cartilage layer in this example is adjusted to a mixture of methacrylated gelatin gel solution, methacrylated hyaluronic acid gel solution, and methacrylated chitosan gel solution in a ratio of 0.9:0.9:1.1. The pore size of the Gyroid structure porous magnesium alloy scaffold is changed to 600 μm, and the other steps are the same as in Example 1.
[0054] Comparative Example 1
[0055] This comparative example refers to Example 1, except that the Gyroid structure porous magnesium alloy bracket is replaced by a solid cylinder with a height of 3.5 mm and a diameter of 5 mm.
[0056] Test Example 1
[0057] The difference between the conventional stacking and the soft-hard combination of the present invention is as follows: Figure 1 As shown. The top is the ordinary stacking of comparative example 1. It can be found that during the compression process, the gel can only deform in all directions, resulting in excessive local deformation; while the bottom is the soft-hard combination of Example 1, which can disperse the pressure of local deformation. In the present invention, we compared the compression modulus test of placing the gel on a solid support and on a porous support to observe whether the Gyroid porous structure below improves the mechanical properties of the upper gel. Figure 2As shown, we selected a deformation of 25% as the ASTM standard during the compression process to determine the elastic modulus (Young's modulus): E = Stress / Strain. The Young's modulus of normal physiological cartilage: 0.5-1.5MPa. It can be found that when the bottom is a solid platform, the Young's modulus is only 0.190MPa, which is about 3 times different from the normal cartilage strength. After adding a porous scaffold at the bottom, due to the buffering effect of the special structure, the Young's modulus is increased to 0.476MPa, which is more in line with the strength of physiological cartilage. In addition, it was found that during the compression process, the sample of comparative example 1 broke at a deformation of 33%, and with the support of the soft-hard combination structure, the sample of Example 1 broke at a deformation of 43%, which greatly improved the compression resistance. Referring to the above preparation method, Example 2 and Example 3 were tested, and the Young's modulus of the sample of Example 2 was measured to be 0.468MPa, and the Young's modulus of the sample of Example 3 was measured to be 0.474MPa.
[0058] Test Example 2
[0059] The present invention also conducted a fatigue stress test on a special structure combining soft and hard, simulating the compression-recovery process of normal cartilage, measuring the Young's modulus at the 0th, 500th and 5000th times, and comparing the change of its Young's modulus at the moment of 25% deformation at the 5000th time, as shown in FIG. Figure 3 As shown, it can be found that the Young's modulus of comparative example 1 was reduced from 0.190MPa to 0.068MPa, further reducing the mechanical strength of the cartilage layer, while the Young's modulus of the soft-hard combination group was only reduced from 0.476MPa to 0.366MPa. It can be seen that the porous structure below has a significant buffering effect on the cartilage layer.
[0060] Test Example 3
[0061] The combination of soft and hard is not only reflected in the physical level of bonding and performance improvement, but also has a stronger bonding effect at the electrochemical level. Figure 4 As shown in the figure, through infrared spectroscopy analysis, we found that after the soft-hard combination, the peak width and peak shape of the C=O and OH bonds changed, which may be due to the Mg released by the hydrogel in the magnesium alloy. 2+ After binding, coordination occurs, resulting in changes in the stretching vibration frequency, which causes an increase in peak width and a change in peak shape; the increase in peak width also means that the hydrogen bonding effect on the binding surface is enhanced, and the molecules on the binding surface may be rearranged to form a stronger hydrogen bond network; 1630 is the characteristic peak of water molecules, and 1720 is the characteristic peak of HAMA carbonyl groups, indicating that more water molecules are locked in the binding layer. The reduction in free water molecules will also make the soft and hard binding interface more tightly bonded.
[0062] Test Example 4
[0063] In order to verify the performance of the hydrogel used in the present invention, this test example tests other hydrogels used alone and hydrogels combined in pairs, as shown below:
[0064] Methacrylylated gelatin gel solution, methacrylylated hyaluronic acid gel solution and methacrylylated chitosan gel solution were prepared respectively according to the method in Example 1. Then various samples were prepared respectively according to the following methods, and 6 samples of each sample were prepared for testing.
[0065] The methacrylated gelatin gel solution, the methacrylated hyaluronic acid gel solution, and the methacrylated chitosan gel solution were mixed in a ratio of 1:1:1, and then transferred to a cylindrical mold with a height of 1.5 mm and a diameter of 5 mm. A 405 nm ultraviolet light source was used to irradiate for 20 s to cure the photocurable groups in the mixed gel to obtain a Mix sample.
[0066] The methacrylated gelatin gel solution was transferred to a cylindrical mold with a height of 1.5 mm and a diameter of 5 mm, and irradiated with a 405 nm ultraviolet light source for 20 s to solidify the photocurable groups in the mixed gel to obtain a GelMA sample;
[0067] The methacrylated hyaluronic acid gel solution was transferred to a cylindrical mold with a height of 1.5 mm and a diameter of 5 mm, and irradiated with a 405 nm ultraviolet light source for 20 seconds to cure the photocurable groups in the mixed gel to obtain a HAMA sample;
[0068] The methacrylated chitosan gel solution was transferred to a cylindrical mold with a height of 1.5 mm and a diameter of 5 mm, and irradiated with a 405 nm ultraviolet light source for 20 s to cure the photocurable groups in the mixed gel to obtain a CSMA sample;
[0069] The methacrylated gelatin gel solution and the methacrylated hyaluronic acid gel solution were mixed in a ratio of 1:1, and then transferred to a cylindrical mold with a height of 1.5 mm and a diameter of 5 mm. A 405 nm ultraviolet light source was used to irradiate for 20 seconds to cure the photocurable groups in the mixed gel to obtain a HAMA-GelMA sample.
[0070] The methacrylated gelatin gel solution and the methacrylated chitosan gel solution were mixed in a ratio of 1:1, and then transferred to a cylindrical mold with a height of 1.5 mm and a diameter of 5 mm. A 405 nm ultraviolet light source was used to irradiate for 20 seconds to cure the photocurable groups in the mixed gel to obtain a CSMA-GelMA sample. The above samples were tested for performance:
[0071] Figure 5That is, the test of G' and G", where G' is the storage modulus, which indicates the energy stored in the material during the cyclic deformation process. The higher G', the better the elasticity; G" is the loss modulus, which indicates the energy lost by the material during the cyclic deformation process. The higher G", the stronger the viscosity and the greater the loss. The yellow area in the figure is the photocuring process. This study calculated the G' / G" ratio of each component gel after curing. The experiment found that although the two moduli of HAMA single component were the highest, the ratio was low, resulting in its brittle material, which was not easy to recover during repeated elastic compression and did not meet the requirements of cartilage properties. In general, the three-component (Mix) gel has a better comprehensive evaluation in terms of both absolute value and ratio, and is a more suitable choice as a cartilage gel component.
[0072] In addition, this test example also carried out the detection of various instantaneous Young's moduli, such as Figure 6 As shown, we use compression to 30% deformation as the measurement point. It can be observed that although the Young's modulus of the HAMA group is the highest among all groups, followed by the Mix group samples, the Young's modulus of other samples is significantly lower than that of the HAMA group and the Mix group. However, due to the brittle nature of the HAMA group, it cannot recover after compression, and 4 of the 6 samples were broken, while none of the 6 samples of the Mix group gel were broken. In summary, the mixed gel of the three components used in the present invention is more in line with the needs of cartilage phase hydrogel.
[0073] Obviously, the above embodiments are merely examples for clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from them are still within the protection scope of the invention.
Claims
1. A magnesium alloy hydrogel composite stent, characterized in that: include: A magnesium alloy bracket having a porous structure; A hydrogel cartilage layer, the surface of which is in contact with the magnesium alloy stent, and the hydrogel cartilage layer comprises methacrylated gelatin hydrogel, methacrylated hyaluronic acid hydrogel and methacrylated chitosan hydrogel.
2. The magnesium alloy hydrogel composite scaffold according to claim 1, characterized in that: The portion of the hydrogel cartilage layer in contact with the magnesium alloy support is embedded in the holes on the surface of the magnesium alloy support through deformation.
3. The magnesium alloy hydrogel composite scaffold according to claim 1, characterized in that: The pore size of the magnesium alloy support is in the range of 300-600 μm.
4. The magnesium alloy hydrogel composite scaffold according to claim 1, characterized in that: The magnesium alloy stent is a porous magnesium alloy stent with a Gyroid structure.
5. The magnesium alloy hydrogel composite scaffold according to claim 1, characterized in that: The magnesium alloy bracket comprises the following components by mass fraction: Mg: 96.5-97%; O:0.9~0.92%; Y:1.05~1.15%; Nd: 0.80~0.85%; Zr:0.08~0.12%; Gd: 0.3~0.33%.
6. The magnesium alloy hydrogel composite scaffold according to claim 1, characterized in that: The water content of the methacrylic gelatin hydrogel, the methacrylic hyaluronic acid hydrogel and the methacrylic chitosan hydrogel are all 85-95%.
7. The magnesium alloy hydrogel composite scaffold according to claim 1, characterized in that: The weight ratio of methacrylylated gelatin hydrogel: methacrylylated hyaluronic acid hydrogel: methacrylylated chitosan gel hydrogel in the hydrogel cartilage layer is 0.9-1.1: 0.9-1.1: 0.9-1.
1.
8. The magnesium alloy hydrogel composite scaffold according to claim 1, characterized in that: The preparation method of the hydrogel cartilage layer comprises the following steps: Step 1) using an aqueous solution containing a light curing agent to dissolve methacrylated gelatin dry powder, methacrylated hyaluronic acid dry powder, and methacrylated chitosan dry powder respectively to obtain methacrylated gelatin gel solution, methacrylated hyaluronic acid gel solution, and methacrylated chitosan gel solution; Step 2) Mixing the methacrylated gelatin gel solution, the methacrylated hyaluronic acid gel solution and the methacrylated chitosan gel and subjecting them to photocuring treatment to obtain the hydrogel cartilage layer.
9. The magnesium alloy hydrogel composite scaffold according to claim 1, characterized in that: The magnesium alloy stent and the hydrogel cartilage layer are both cylindrical; the top surface of the magnesium alloy stent is in contact with the bottom surface of the hydrogel cartilage layer.
10. A device for repairing osteochondral defects, characterized in that: The invention comprises the magnesium alloy hydrogel composite stent according to any one of claims 1 to 9.
Citation Information
Cited By
Bionic magnesium alloy material for inducing bone-cartilage synchronous regeneration and preparation method thereof
CN121971695A
Biodegradable magnesium slow-release hydrogel, preparation method thereof and application of biodegradable magnesium slow-release hydrogel in preparation of tumor postoperative adjuvant therapy products
CN122031363A